2003
DOI: 10.3168/jds.s0022-0302(03)73740-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Rennetability of Heated Milk; Study of Enzymatic Hydrolysis and Gelation Kinetics

Abstract: Casein micelles in milk are stable colloidal particles with a stabilizing hairy brush of kappa-casein. During cheese production rennet cleaves kappa-casein into casein macropeptide and para-kappa-casein, thereby destabilizing the casein micelle and resulting in aggregation and gel formation of the micelles. Heat treatment of milk causes impaired clotting properties, which makes heated milk unsuitable for cheese production. In this paper we compared five different techniques, often described in the literature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 23 publications
(48 reference statements)
7
94
0
Order By: Relevance
“…This reaction is relatively well described on whey proteins but not on casein micelles. The technological consequences of heat treatment are multiple and described in different reviews, book chapters, and specific articles (Lucey et al 2001;Vasbinder et al 2003;Raikos 2010;Kethireddipalli et al 2010;Dalgleish and Corredig 2012). The most well-known consequence of milk heat treatment is its loss of coagulability by rennet with an increase of the time of gelation and a decrease of gel firmness.…”
Section: Heatingmentioning
confidence: 99%
“…This reaction is relatively well described on whey proteins but not on casein micelles. The technological consequences of heat treatment are multiple and described in different reviews, book chapters, and specific articles (Lucey et al 2001;Vasbinder et al 2003;Raikos 2010;Kethireddipalli et al 2010;Dalgleish and Corredig 2012). The most well-known consequence of milk heat treatment is its loss of coagulability by rennet with an increase of the time of gelation and a decrease of gel firmness.…”
Section: Heatingmentioning
confidence: 99%
“…Van Hooydonk et al [154] and Vasbinder et al [158] also reported a large inhibitory effect of the heat-treatment of milk on the secondary phase of the rennet action, i.e., on the aggregation and gelation of the casein micelles. As a consequence of their coating by denatured whey proteins, the casein micelles of heated milk have a lower surface hydrophobicity [92], thus lowering the potential for interaction.…”
Section: F Guyomarc'hmentioning
confidence: 99%
“…Heat-treatment [162] and alkalinisation of the milk [153] both decrease the proportion of soluble calcium (and phosphate) ions, thus increasing the detrimental effects of these changes on the formation of rennet gels, although one application of alkaline heat-treatment in order to reduce milkstone can be mentioned [46]. However, the effects of calcium and phosphate changes on the inhibition of the rennet action in heated milk are generally regarded as lower than those induced by the formation of heat-induced protein aggregates on the surface of the casein micelles [95,154,158], albeit this is still debated [133].…”
Section: F Guyomarc'hmentioning
confidence: 99%
“…The adverse effects on coagulation are attributed to the inhibition of hydrolysis of κ-casein by chymosin due to the β-lactoglobulin/κ-casein complex at the micelle surface impairing the accessibility of κ-casein to the coagulant [55,59,139], to reduced reactivity of renneted micelles with attached denatured whey proteins to aggregation, or to a reduction in the concentration of micellar calcium [139,142]. Reduced shrinkage of the para-caseinwhey protein network promotes increased water-binding [145], leading to poor coagulation and syneresis properties, increased set-to-cut times, soggy curds with poor matting ability, ragged curd chips and poor curd fusion during cheese manufacture [48,92].…”
Section: Heat Treatments Other Than Pasteurisationmentioning
confidence: 99%